2013
DOI: 10.5863/1551-6776-18.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide for Weight Loss in Adolescents

Abstract: Obesity in children and adolescents is a growing epidemic in the United States, and physicians are increasingly looking for safe and effective treatments. In recent years, pharmacologic treatment has been considered for severe and refractory cases of adolescent obesity. We present a case of an obese adolescent who presented to an inpatient psychiatric unit with a body mass index (BMI) of 37.8 (>98th percentile for age). He was started on zonisamide for the purposes of weight loss, and a steady decrease in weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…That being said, there are a few case reports that match our findings and indicate that zonisamide also contributes to weight reduction in children and adolescents. 41,42 Considering that our findings suggest that these anticonvulsants are effective for weight reduction even when patients are gaining a significant amount of weight from antipsychotics, both anticonvulsants are promising agents for future research into how to counteract weight gain associated with antipsychotics commonly observed in psychiatric clinics.…”
Section: Discussionmentioning
confidence: 88%
“…That being said, there are a few case reports that match our findings and indicate that zonisamide also contributes to weight reduction in children and adolescents. 41,42 Considering that our findings suggest that these anticonvulsants are effective for weight reduction even when patients are gaining a significant amount of weight from antipsychotics, both anticonvulsants are promising agents for future research into how to counteract weight gain associated with antipsychotics commonly observed in psychiatric clinics.…”
Section: Discussionmentioning
confidence: 88%
“…Zonisamide is an antiepileptic medication approved by the FDA as an adjunct therapy in partial seizures for adolescents of 16 years and adults [ 100 ]. The addition of zonisamide to treating a 15-year-old obese male admitted to the hospital for depression and anxiety symptoms resulted in appetite suppression by acting on the hypothalamus, weight loss and normalization of his triglyceride levels [ 101 ]. In addition, results from clinical trials investigating the effect of zonisamide as add-on therapy in children suffering from partial seizures on weight reduction showed that about 35.8% of the treated patients experienced significant weight reduction (≥5% reduction of body weight) [ 102 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Adult patients have experienced weight loss with the use of zonisamide 57 . A small number of pilot data have shown that zonisamide may potentially be effective for weight loss in the paediatric population 116,135 . Further research is required to investigate the efficacy and safety of this medication for weight loss in children and young people.…”
Section: Definitionmentioning
confidence: 99%